Respuesta :

Answer:  5 units

Work Shown:

[tex]A = (x_1,y_1) = (-3,2) \text{ and } B = (x_2, y_2) = (-6,-2)\\\\d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}\\\\d = \sqrt{(-3-(-6))^2 + (2-(-2))^2}\\\\d = \sqrt{(-3+6)^2 + (2+2)^2}\\\\d = \sqrt{(3)^2 + (4)^2}\\\\d = \sqrt{9 + 16}\\\\d = \sqrt{25}\\\\d = 5\\\\[/tex]

I used the distance formula. Alternatively, you can plot the two points and form a right triangle. Then use the pythagorean theorem. The distance formula is effectively a modified version of the pythagorean theorem.

ACCESS MORE